AVAILABILITY AND OVERLAP OF QUALITY COMPUTER SCIENCE JOURNAL HOLDINGS IN SELECTED UNIVERSITY LIBRARIES IN MALAYSIA - Ling, Ng Siew; Awang Ngah, Zainab (Malaysian Journal of Library and Information Science, 2003)
The study reveals the availability status of quality journals in the field of computer science held in the libraries of the University of Malaya, (UM), University of Science Malaysia (USM), University of Technology Malaysia (UTM), National University of Malaysia (UKM) and University Putra Malaysia (UPM). These universities are selected since they offer degree programmes in computer science. The study also investigates the degree of overlaps and unique titles in the five libraries. The University of Malaya Library was taken as a case study to show how total overlap titles are calculated, and how possible savings and wider coverage of quality journals could be achieved if cooperative acquisition scheme is practiced. Quality journals in the study are 301 titles with calculated impact factor listed by the Journal Citation Report (JCR). The results indicate that (a) the title availability ranges from poor to very poor with 40% by UTM, 34.22% by UM, and 16% by UKM: (b) out of the 301 titles, 115 (38.2%) are overlaps, 96 titles (32.23%) are unique titles and 89 titles are not subscribed; (c) the percentage of unique titles and overlaps are related to the size of title availability; (d) journal titles subscribed increased by more than 50% each year (e) the cost of journal title overlaps for UM library is estimated to be about US163,170.60. This cost could be reduced and a wider coverage of unique titles could be achieved if the five libraries cooperatively acquire high impact journal titles.